Agency costs, board structure and institutional investors: case of India - Pankaj Chaudhary (Emerald Publishing Limited, 2021)
The author examines the role of board structure and institutional investors in dealing with the agency issues for the Indian firms by taking the data of NSE-500 nonfinancial firms for the period 2010–2019.The author applies dynamic panel data methodology to deal with endogeneity concerns prevalent in corporate finance variables.The agency view is consistent with the board size in the context of India. The author observed that the board size has a harmful effect on agency cost. A larger board size may create a coordination problem, or CEO may find it easy to thrust his or her decisions on board. The author also noticed that firms should have sizeable institutional ownership, particularly pressure-insensitive investors, in equity as they can reduce agency-related issues.This study focuses on one of the largest emerging economies, i.e. India.